N-Acetyl chitooligosaccharides attenuate amyloid β-induced damage in animal and cell models of Alzheimer's disease. (September 2019) - Jiang, Zhiwen; Liu, Guijuan; Yang, Yan; Shao, Kai; Wang, Yanting; Liu, Wanshun; Han, Baoqin
Graphical abstract: Highlights: Animal and cell models of Alzheimer's diseas (AD) were established. Learning and memory ability of AD rat was improved by N-acetyl chitooligosaccharides. NA-COS attenuated Amyloid β-generated cytotoxicity on PC-12 cells. NA-COS showed great potential as new functional food ingredient to prevent AD. Abstract: Alzheimer's disease (AD), usually characterized by progressive deteriorates of intellectual and social functions, memory loss and cognitive impairment, is symptomatized by the neurotoxic effect of oligomers of amyloid beta (Aβ). In this study, the activities of N-acetyl chitooligosaccharides (NA-COS), the hydrolytic products of chitin, were evaluated using Aβ-induced damages in animal and cell models of AD. Our results demonstrated that NA-COS significantly improved both acquisition (learning) and retention (memory) of AD rats on water maze task. HE staining of brain tissue sections showed that NA-COS could ameliorate hippocampal neurodegeneration induced by Aβ25–35 . Further biochemical analysis showed that NA-COS treatment of intrahippocampal Aβ-microinjected rats was able to elevate choline acetyltransferase activity and attenuate hippocampal acetylcholinesterase and malondialdehyde contents. Superoxide dismutase and glutathione peroxidase levels in the hippocampus homogenate of rats after NA-COS treatment were much higher when compared with AD rats. Moreover, the Aβ25–35 (100 μmol/l) treatment reduced viability and induced apoptosis in rat adrenal gland pheochromocytoma cells (PC-12). Treatment with NA-COS had significantly attenuated Aβ-generated cytotoxicity on PC-12 cells by maintaining higher cell viability and elevating Bcl-2 expression. Therefore, it could be concluded that NA-COS showed great potential as new functional food ingredient to prevent neurodegenerative diseases.